1998
DOI: 10.1063/1.1149198
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined silicon torsional resonator for magnetic anisotropy measurement

Abstract: A novel method for measuring the out-of-plane magnetic anisotropy of thin films has been developed using the existing techniques of silicon micromachining. The torsion pendulum, which is commonly used to measure the perpendicular magnetic anisotropy energy constant, Ku, is modified into a single crystal silicon high Q torsional resonator. This article describes the principle of a silicon torsional resonator, the experimental procedure for measuring magnetic anisotropy, and the results. The theoretical values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Torque magnetometry has been performed with macroscopic single-crystal silicon resonators. [1][2][3][4] Smaller structures are being considered for use as chemical sensors, force gauges, 5,6 nano-actuators, 7 magnetic resonance force microscopes, 8 and for various optomechanical and biomedical applications. Small resonant structures also open fascinating avenues for mesoscopic studies of the mechanical properties of materials, [9][10][11][12] and of interesting parametric amplification effects.…”
Section: Introductionmentioning
confidence: 99%
“…Torque magnetometry has been performed with macroscopic single-crystal silicon resonators. [1][2][3][4] Smaller structures are being considered for use as chemical sensors, force gauges, 5,6 nano-actuators, 7 magnetic resonance force microscopes, 8 and for various optomechanical and biomedical applications. Small resonant structures also open fascinating avenues for mesoscopic studies of the mechanical properties of materials, [9][10][11][12] and of interesting parametric amplification effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that the coercivity in the direction perpendicular to the film plane is higher (385 Oe) than in the in-plane direction (170 Oe), which indicates an existence of biaxial anisotropy in this film. It has been shown that the major sources of the anisotropy in amorphous Terfenol-D films are the stress-induced anisotropy and the shape anisotropy [6]. We believe that the mismatch in the thermal expansion coefficient between PMN-PT (20×10 -6 /°C) and Terfenol-D (12×10 -6 /°C) gives rise to a residual compressive stress when the film is cooled from its deposition temperature of 200 °C to room temperature.…”
Section: Methodsmentioning
confidence: 95%
“…A similar instrument has been used to measure out-ofplane anisotropy K of thin magnetic films, described by Morillo et al 18 In this mode of operation the shifts in the torsion resonance frequency caused by the magnetic stiffening of a torsion oscillator are measured as a function of applied field. Future prospects include combining M -H and K measurements into one instrument.…”
Section: ͑1͒mentioning
confidence: 99%